The revolving door : evidence from the United Kingdom, Germany, France, Spain, Belgium, Greece and Brazil - Dias, A.C. (2015)
The following study analyses the academic background and careers of 175 members of Governments and Central Banks of seven countries (Belgium, Brazil, France, Germany, Greece, Spain and United Kingdom) for the years 1975 and 2015, in order to verify whether the “Revolving Door Theory” can be applied to these cases. After some research on the curricula vitae of the members of Governments and Central Banks, we found that, for instance, that more Government and Central Bank members studied abroad for the case of the UK and US than for the other countries. We also found that it is more common for Central Bank executive members to obtain PhDs than it is the case for Government members. Moreover, external promotions in the Central Banks in 1975 were quite relevant but no cases were registered for 2015; for Governments, the trend was the exact opposite, no external promotions in 1975 but many cases in 2015. While it is not possible to find irrefutable evidence to sustain the Revolving Door hypothesis, it is still possible to find recurrent patterns in different countries that may be explained by that theory. More expanded databases and a larger selection of countries is required for that analysis.